Rapid Method for Species-Specific Identification and Determination of Toxigenicity of Vibrio Cholerae from Natural Aquatic Environment (Stamford Journal of Pharmaceutical Sciences, 2009)
Cholera caused by toxigenic Vibrio cholerae is a major public health problem confronting developing countries, where outbreaks occur in a regular seasonal pattern and are particularly associated with poverty and poor sanitation. It is generally accepted that seven distinct pandemics of cholera have occurred since the onset of the first pandemic in 1817. Again Vibrio cholerae is capable of surviving in aquatic environments for extended periods and is considered as autochthonous species in estuarine and brackish waters. Therefore, the present study was designed to isolate V. cholerae from natural environmental samples subsequently identified by conventional and molecular biological techniques. A total number of 10 isolates were included randomly in this study based on their initial identification. The serotypes of the isolates were determined by serological test (slide agglutination) and the number of serotypes O1, O139 and non-O1/O139 were 3, 2 and 5 respectively which were reconfirmed by PCR method. Finally, the toxigenicity of the isolates was analyzed by multiplex PCR method and five (5) isolates were found to contain the ctx gene, the major virulence factor of V. cholerae. Key Words: Vibrio cholerae, Simplex PCR, Multiplex PCR, Serotypes, Toxigenicity. Â  doi:10.3329/sjps.v1i1.1811 S. J. Pharm. Sci. 1(1&2): 69-75